(3aJM GdYRjR Ydi cJGH GdhLjRs - (3YHO GdcQje Hf eMeO Hf YHO GdcQje, CHh GdbGSe GdQGaYj GdbRhjfj,J (B623 (3g` s ((3CMeO Hf eMeO Hf YHO GdQMje GdCehi GdTGaYi s)
(3ChdgG (B:s
(3jHOC HcJGH GdEbQGQ s
(3BNQgG (B:s
(3bGd hdh Yde Hg hde jQcHg HMGd adG Sge dg hGddg CYde Je QHY GdeYGedGJ HMeO Gddg hYhfg hMSf dWag s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQM s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B55 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B3s
Keywords: (3Gdabg GdTGaYjs